Marker assisted selection for developing superior breeding lines for white rust resistance in Indian mustard (Brassica juncea) using IP markers - Disha Kamboj; Neelam R Yadav; Neelam R Yadav; Ram Avtar (Journal of Oilseed Brassica, 2026)
White rust caused by Albugo candida is one of the significant diseases for yield reduction in rapeseed-mustard.Molecular marker technology in combination with the traditional breeding method offers precise selection in cropimprovement programme. RH0749 a commercial and susceptible variety of Indian mustard was crossed with resistantdonors (Bio-YSR and BEC-144) for improving white rust resistance. BC1F1, BC2F1 populations were evaluated for variousyield attributes and analysed at molecular level to undertake marker-assisted selection (MAS). Intron polymorphism andcleaved amplified polymorphic sequence markers were used for forward selection. Three IP markers in RH0749 × Bio-YSRcross and two IP markers in RH0749 × BEC-144 cross showed polymorphism. Three hundred and forty-eight SSRs wereused for background selection and 72 SSR markers were found polymorphic in RH0749 × Bio-YSR cross while in RH0749× BEC-144 cross, only 43 SSR markers were found polymorphic. The promising progenies (9 in BC2F1 for RH0749 × Bio-YSR and 8 in BC2F1 for RH0749 × BEC-144 cross) were selected based on molecular, morphological and disease datawhich can be further used in Indian mustard improvement programme for white rust resistance.